Sistem Pemantauan Kualitas Udara Berbasis IoT di Lingkungan Kampus Politeknik Negeri Medan - Nurhafni Carol (CV. Hawari, 2025)
This research aims to design and implement an Internet of Things (IoT)-based air quality monitoring system in the Medan State Polytechnic Campus. Given the importance of air quality for the health and comfort of the academic community, the system is designed to monitor air quality parameters such as PM2.5 concentration, CO2, and temperature in real-time. The developed system uses sensors integrated with microcontrollers and wireless communication modules to transmit data to the cloud platform. The collected data will be analyzed and displayed through a mobile application, which allows users to access air quality information at various locations within the campus directly. The test results show that the system can provide accurate data with a fast response rate, as well as the ability to identify patterns of changes in air quality. Feedback from users shows that this system is very helpful in raising awareness of the importance of air quality and its impact on health. The conclusion of this study is that the implementation of an IoT-based air quality monitoring system in the Medan State Polytechnic Campus can contribute positively to maintaining the health of the academic community and supporting efforts to sustain the campus environment.